Study of the effect of the ethyl alcohol extract of leaves Carissa mac-rocarpa in the control of the green peach Myzus persicae in vitro - Mutashar, Ali Youssef; Rashid, Yousif Dakheel; Mohammed, Najaha (Journal of Kerbala for Agricultural Sciences, 2022)
The current study evaluated the efficacy of ethyl alcohol extract in the plant leaves of Carissa macrocarpa in the control of green peach aphid Myzus persicae in vitro. The results showed the effect of using different concentrations of the ethyl alcohol extract of the plant leaves of C. macrocarpa on the mortality average rate of nymphs and adults of green peach aphid M. persicae in the laboratory, as the highest mortality rate on the nymphs and adults reached 64.11% and 53.56% at the concentration of 100 mg/ml, respectively, while the lowest mortality level was 54.11% and 32.78% at the concentration of 50 mg/ml, respectively. There were significant differences in the mortality rate.